2013
DOI: 10.1007/s00262-013-1450-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD14+HLA-DR-/low myeloid-derived suppressor cells correlate with extrathoracic metastasis and poor response to chemotherapy in non-small cell lung cancer patients

Abstract: Accumulating evidence has demonstrated that myeloid-derived suppressor cells (MDSCs), a heterogeneous population of cells, play an important role in the subversion, inhibition, and downregulation of the immune response to cancer. However, the characteristics of these cells, particularly clinical relevance, in malignant tumors remain unclear due to a lack of specific markers. In this study, we characterized peripheral CD14(+)HLA-DR(-/low) cells, a new human MDSC subpopulation, in 89 patients with non-small cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
147
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(160 citation statements)
references
References 45 publications
11
147
1
1
Order By: Relevance
“…It is well documented that MDSCs and TAMs are associated with poor clinical outcome in patients with solid tumors (22)(23)(24). In human neuroblastoma, tumor-infiltrating inflammatory myeloid cells were analyzed by immunohistochemistry stainings in 133 metastatic tumors and demonstrated independent prognostic values (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that MDSCs and TAMs are associated with poor clinical outcome in patients with solid tumors (22)(23)(24). In human neuroblastoma, tumor-infiltrating inflammatory myeloid cells were analyzed by immunohistochemistry stainings in 133 metastatic tumors and demonstrated independent prognostic values (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, tumor-induced inflammation limits efficient antitumor immune responses through recruitment of various suppressive immune cell types (15), including myeloidderived suppressor cells (MDSC) and "M2-biased" tumor-associated macrophages (TAM) (16)(17)(18)). These cells demonstrate overlapping phenotypic markers as well as inhibitory mechanisms (19,20) and predict poor clinical outcome in patients with cancer (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…In melanoma, MDSCs are associated with tumor progression, signs of EMT such as decreased E-Cadherin expression and increased migratory capacities of malignant cells 36 . Similarly, MDSCs may contribute to metastatic dissemination of different types of cancer, including NSCLC 43 . Finally, Srivastava’s team demonstrated that when MDSCs were depleted, the size of tumors decreased and cell migration was reduced 44 .…”
Section: Discussionmentioning
confidence: 99%
“…29-34 In patients with non-small cell lung cancer, both frequency and the absolute number of peripheral CD14 + HLA-DR −/low MDSCs subset were significantly increased compared with healthy controls and were associated with metastasis, response to chemotherapy and progression-free survival. 35 In patients with terminal cancer, peripheral blood levels of granulocytic MDSCs correlated with overall survival. Patients with low levels of CD15 + CD16 low cells had significantly longer survival times and patients with high levels of CD15 + CD16 low cells tended to have poor performance status.…”
Section: Discussionmentioning
confidence: 99%